PTH-093 Outcomes following the introduction of week 12 anti-tnf drug and antibody testing in patients with inflammatory bowel disease. (17th June 2017) - Boal, A; Squires, SI; Naismith, GD
Abstract : Introduction: The use of anti-TNF drug and antibody testing has increased in clinical practice. Recent NICE guidance has advocated further research into clinical outcomes associated with testing. This report describes outcomes following the introduction of drug level and antibody testing (TDM) to our 12 week assessment criteria in treatment naïve patients. Method: In July 2015 the Royal Alexandra and Vale of Leven Hospitals introduced TDM as part of the clinical assessment of all patients commencing anti-TNF therapy. Those with previous anti-TNF exposure were excluded. Between July 2015 and December 2016, Infliximab (IFx) and Adalimumab (ADA) levels were measured at week 12. 54 patients commenced ADA (37 Crohns vs 17 Ulcerative Colitis) and 20 commenced IFx (7 Crohn's disease vs 13 Ulcerative Colitis). In total 74 patients had TDM checked, in addition to symptom assessment and CRP measurement. The results were sub-categorised to determine patients with drug levels greater than or equal to 3 µg/mL [Group 1- therapeutic], less than 3 µg/mL, but greater than 0.8 µg/mL [Group 2-subtherapeutic] and less than 0.8 µg/mL [Group 3-undetectable]. Results: Group 1 had 62/74 (84%) with therapeutic levels. 3/62 (5%) developed antibodies. 54/62 (87%) reported good symptom control. There was a reduction in mean CRP of 87% over 12 weeks. 8/62 (13%) were symptomatic at week 12 and assessment by colonoscopy determined active disease, despite therapeutic levels. Group 2 had 4/74 (5%) with subtherapeutic levels. 1/4 (25%) developed antibodies. 1/4 (25%) had dose increase in therapy. 1/4 (25%) had therapy withdrawn (in remission). 2/4 (50%) were maintained on current dose. There was a reduction in mean CRP of 24% over 12 weeks. Group 3 had 8/44 (11%) with undetectable levels. 6/8 (75%) developed antibodies. 4/8 (50%) were withdrawn from treatment following assessment. 4/8 (50%) had active disease on colonoscopy and had a change of biological agent. There was a reduction in mean CRP by 20% over 12 weeks Conclusion: At 12 weeks 16% of patients in this cohort had sub therapeutic or undetectable drug levels. This prompted further assessment, which facilitated either an early switch of therapy or treatment withdrawal. There is a lower level of antibody formation in the therapeutic and subtheraputic groups and greater reduction in CRP in the therapeutic group. 12 week TDM measurement appears to be a worthwhile addition to standard assessment. Disclosure of Interest: None Declared